HARMONISASI PENGATURAN HUKUM INVESTASI SURAT BERHARGA DAN INVESTASI LANGSUNG MENURUT UNDANG-UNDANG NOMOR 4 TAHUN 2023 TENTANG PENGEMBANGAN DAN PENGUATAN SEKTOR KEUANGAN (P2SK) DAN PERATURAN PEMERINTAH NOMOR 63 TAHUN 2019 TENTANG INVESTASI PEMERINTAH - Makruf, Solihan; Anwari, Amalia Nur; Aula, Muhammad Iqbal; Yusup, Deni Kamaludin (Jurnal Ilmiah Dinamika Hukum, 2026)
This study is motivated by the fact that the regulation of securities investment and direct investment in Indonesia still faces legal harmonization issues between the provisions of Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector particularly those governing the capital market and Government Regulation No. 63 of 2019 concerning Government Investment. This research aims to analyze the compatibility, substantial differences, and legal implications of the two regulations in the context of establishing an integrated and equitable investment legal system. This study applies a normative juridical approach with a descriptive analysis method. Data were collected using a literature study technique through a review of legislation, legal literature, and related policy documents. Furthermore, the data was analyzed using qualitative data analysis techniques with an emphasis on systematic interpretation and the principle of harmonization of laws and regulations. The results of this study indicate that there is still a lack of synchronization between the regulation of securities investment in the capital market and the mechanism of direct investment by the government, particularly in terms of authority, risk management, and legal accountability. The findings of this study imply the need for improvements to derivative regulations and implementation guidelines that are capable of integrating capital market legal principles with government investment policies in order to create legal certainty and effective management of national investments. Keywords: Legal Harmonization, Securities Investment, and Government Investment